The Implementation of Green Roof Buildings Towards Sustainable Environmental in Kuala Lumpur: Key Player Perspective - Law Jing Wei; Khalid, Zailawati; Seow Ta Wee; Md Asrul Nasid Masrom; Norazah Attan (Research in Management of Technology and Business, 2025)
Rapid population growth and urbanization have intensified environmental challenges, including excessive greenhouse gas emissions, and urban heat island effects driven by the construction sector’s energy demands and the loss of green spaces. Therefore, the study aims to identify the factors of green roof implementation towards sustainable environmental, to investigate the challenges and strategies to enhance the implementation of green roof in Kuala Lumpur. This study employed a qualitative method, with primary data collected through semi-structured interviews with experts in green roof building. The qualitative data collected from the semi-structured interviews analyzed using thematic analysis techniques. The identified themes organized and analyzed to develop a comprehensive understanding the factors of green roof implementation towards sustainable environmental, challenges and strategy to enhance the green roof implementation in Kuala Lumpur. The research focused on five respondents with significant experience in green roof projects, including project managers, green roof building consultants, and architects involved in green roof construction within Kuala Lumpur, to ensure reliable insights. The findings reveal that green roofs contribute significantly to sustainability by reducing carbon emissions, improving energy efficiency, and managing urban heat islands. Despite these benefits, challenges such as high installation and maintenance costs, water retention issues, and limited public awareness hinder widespread adoption. Strategies proposed include government incentives, public education, and integrating green roofs into standard construction practices. The study provides valuable recommendations for policymakers, construction professionals, and urban planners to promote green roofs as a sustainable solution, enhancing environmental quality and urban resilience in Kuala Lumpur.